PENERAPAN MODEL PEMBELAJARAN PAIKEM UNTUK MENINGKATKAN KETERAMPILAN MENCETAK TINGGI DENGAN BAHAN ALAMI SISWA KELAS II SEKOLAH DASAR NEGERI 177 PEKANBARU - Elsa Mai Sarah Hasibuan; Zariul Antosa; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractIssues raised in this research is to improve the skills of high printing with naturalmaterials Elementary School second grade 177 Pekanbaru. Subjects in this studywere second grade students of SDN 177 Pekanbaru academic year 2013/2014 thenumber of 30 students. This research was conducted in two cycles. This study is aclassroom action research (CAR), which aims to improve the skills of highscoringsecond grade natural ingredients SDN 177 Pekanbaru. These resultsindicate that the application of learning models to improve skills PAIKEM scoredhigh with second grade natural ingredients SDN 177 Pekanbaru. At baseline theaverage value of 55.1 students scored higher on the assessment results withnatural ingredients in the first cycle, the average value of 72.7 students increasedby 17.6 from the preliminary data. While scoring high on the assessment resultswith natural ingredients second cycle students' average score increased to 86.33and 13.63 increased by the high scoring of the assessment results with naturalingredients cycle I. This shows that the application of learning models to improveskills PAIKEM scored high with second grade natural ingredients SDN 177Pekanbaru.